Analisis Kemampuan Literasi Bahasa Siswa Sd Di Kota Sawahlunto - Rezky Roganda; Deny Firmaizal; Romi Alviron; Rizky Fitrialdi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to analyze the language literacy skills of elementary school students in Sawahlunto City based on the 2025 Education Report Card data. The research employed a descriptive qualitative approach using a document analysis method. The data source was the Education Report Card containing National Assessment results from three elementary schools, namely SDN 06 Lumindai, SDN 29 Lumindai, and SDN 25 Balai Batu Sandaran. The analyzed data included the percentage of students achieving minimum literacy competency, average school literacy scores, competencies in reading informational and literary texts, and literacy performance based on reading competency levels. Data analysis was conducted through data reduction, data presentation, and descriptive-comparative conclusion drawing. The findings revealed that students' literacy abilities varied across the three schools. SDN 06 Lumindai achieved the highest literacy performance, categorized as good, with 79.31% of students attaining minimum competency and an average literacy score of 62.50. SDN 29 Lumindai was categorized as moderate, with 70.59% of students meeting the minimum competency and an average score of 57.67. Meanwhile, SDN 25 Balai Batu Sandaran recorded the lowest achievement, with only 42.86% of students reaching minimum competency and an average literacy score of 38.10. Further analysis indicated that students were generally more proficient in accessing information than in interpreting and evaluating text content. The findings suggest that instructional quality, school literacy culture, teacher innovation, and the sustainability of literacy programs contribute significantly to students' literacy achievement. Therefore, strengthening systematic and sustainable school literacy programs is essential to improve the language literacy skills of elementary school students in Sawahlunto City.